Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Brain structure–function associations identified in large-scale neuroimaging data - Zhi Yang; Jiang Qiu; Peipei Wang; Rui Liu; Xi-Nian Zuo (Brain Structure and Function, 2016)

Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2016)
Abnormal angiogenesis is critical for portal hypertension in cirrhosis. Except for etiological treatment, no efficient medication or regime has been explored to treat the early stage of cirrhosis when angiogenesis is initiated or overwhelming. In this study, we explored an anti-angiogenesis effort through non-cytotoxic drugs octreotide and celecoxib to treat early stage of cirrhotic portal hypertension in an animal model. Peritoneal injection of thioacetamide (TAA) was employed to induce liver cirrhosis in rats. A combination treatment of celecoxib and octreotide was found to relieve liver fibrosis, portal venous pressure, micro-hepatic arterioportal fistulas, intrahepatic and splanchnic angiogenesis. Celecoxib and octreotide exerted their anti-angiogenesis effect via an axis of cyclooxygenase-2/prostaglandin E2/EP-2/somatostatin receptor-2, which consequently down-regulated phosphorylation of extracellular signal-regulated kinase (p-ERK)–hypoxia-inducible factor-1α (HIF-1α)–vascular endothelial growth factor (VEGF) integrated signaling pathways. In conclusions, combination of celecoxib and octreotide synergistically ameliorated liver fibrosis and portal hypertension of the cirrhotic rats induced by TAA via the inhibition of intrahepatic and extrahepatic angiogenesis. The potential mechanisms behind the regimen may due to the inactivation of p-ERK–HIF-1α–VEGF signaling pathway.

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Re: “PICALM Gene rs3851179 Polymorphism Contributes to Alzheimer’s Disease in an Asian Population” - Ming-Jie Wang; Rui-Ping Liu; Zhi-Jun Kong (NeuroMolecular Medicine, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)